Harriet Kilpatrick Search for Happiness in Emily Henry in the Happy Place - Twissylia Fillarica Nessy; Wahyono, Danu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study, entitled Harriet Kilpatrick’s Search for Happiness in Emily Henry’s Happy Place, explores the main character’s journeyto personal happiness using a psychological approach, specifically Martin Seligman’s PERMA theory. The objective is to examine the causes and effects behind Harriet Kilpatrick’s search for happiness. As a perfectionist and aspiring surgeon, Harriet’s emotional conflict, shaped by her unresolved relationship with Wyn, plays a central role in her internal struggle. The problem statements of this study are: (1) What causes Harriet Kilpatrick’s search for happiness in Happy Place? and (2) What is the effect of Harriet Kilpatrick's search for happiness? Using a qualitative method, the analysis is presented descriptively to explore Harriet’s emotional conflict. The findings reveal that although Harriet initially avoids vulnerability, her journey eventually leads her to fulfill all five elements of happiness within the PERMA model: Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment. By confronting her past and rebuilding meaningful relationships, Harriet achieves a more authentic and lasting sense of personal happiness.